1992
DOI: 10.1016/0735-1097(92)90008-b
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of patients with advanced coronary artery disease after viability studies with positron emission tomography

Abstract: Positron emission tomographic myocardial viability imaging appears to identify patients at increased risk of having an adverse cardiac event or death. Patients with impaired left ventricular function and positron emission tomographic evidence for jeopardized myocardium appear to have the most benefit from a revascularization procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
4
4

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 464 publications
(119 citation statements)
references
References 29 publications
7
104
4
4
Order By: Relevance
“…They differ, however, with respect to the outcome of patients with nonviable myocardium. Whereas in the studies of Eitzman et al, 18 Di Carli et al, 20 and Lee et al, 21 patients with nonviable myocardium had an excellent prognosis (3-year survival, 82% to 100%), these patients definitely had a poorer outcome in our study. Our results are nonetheless in agreement with those of Yoshida and Gould, 22 who used 82 Rb and PET to identify myocardial viability, and with the more recent reports of Pagley et al 23 and Petretta et al, 24 who used thallium scintigraphy as a means of identifying viable myocardium.…”
Section: Prognostic Implications Of Myocardial Ischemia and Viabilitycontrasting
confidence: 72%
See 2 more Smart Citations
“…They differ, however, with respect to the outcome of patients with nonviable myocardium. Whereas in the studies of Eitzman et al, 18 Di Carli et al, 20 and Lee et al, 21 patients with nonviable myocardium had an excellent prognosis (3-year survival, 82% to 100%), these patients definitely had a poorer outcome in our study. Our results are nonetheless in agreement with those of Yoshida and Gould, 22 who used 82 Rb and PET to identify myocardial viability, and with the more recent reports of Pagley et al 23 and Petretta et al, 24 who used thallium scintigraphy as a means of identifying viable myocardium.…”
Section: Prognostic Implications Of Myocardial Ischemia and Viabilitycontrasting
confidence: 72%
“…Risk stratification in patients with LV ischemic dysfunction typically includes a combination of clinical, hemodynamic, and angiographic parameters. 17 Recent studies using myocardial metabolic imaging with positron emission tomography (PET) have indicated that assessing myocardial viability also provides useful prognostic information in these patients, [17][18][19][20][21] with an effect additive to that of the usual clinical assessment. 21 Whereas PET is expensive and not widely available, exercise-redistribution-reinjection thallium scintigraphy and dobutamine echocardiography are less expensive and potentially more widely available methods that can also distinguish viable from nonviable myocardium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 The majority of deaths in these studies were sudden, possibly implicating arrhythmias as being a more common feature in the presence of myocardial hibernation. 9 This combination of segmental wall motion abnormalities and clinically important ventricular arrhythmias could plausibly result from severe disruption in conduction of the depolarizing wave front, leading to asynchronous contraction of individual myocytes and predisposing to reentry arrhythmias.…”
Section: See P 630mentioning
confidence: 92%
“…This is perhaps most important and most relevant in patients with a clinical syndrome of heart failure and a significant degree of global LV dysfunction, a subset of whom will derive considerable benefit in terms of outcome and recovery of LV function after revascularization. Several studies have now suggested that revascularization in the setting of LV dysfunction and significantly retained myocardial viability is associated with an improved natural history [1][2][3][4][5] as well as improvement in heart failure symptoms and functional capacity. 6 Besides providing clinically relevant data, noninvasive scintigraphic and echocardiographic techniques have also helped to illuminate the complex perfusion, metabolic, and functional correlates of these states of reversible LV dysfunction, which remain subjects for debate.…”
mentioning
confidence: 99%